From bowls to pots: The dairying revolution in Northwest Turkey, a view from Barcın Höyük, 6600 to 6000 BCE. - Hadi Özbal; Adria Breu; Laurens Thissen; Fokke Gerritsen; Elisha van den Bos; Alfred Galik; Turhan Doğan; Muhiddin Çergel; Adnan Şimşek; Ayla Türkekul; Rana Özbal (PLoS ONE)
Research has identified Northwest Turkey as a key region for the development of dairying in the seventh millennium BCE, yet little is known about how this practice began or evolved there. This research studies Barcın Höyük, a site located in Bursa's Yenişehir Valley, which ranges chronologically from 6600 BCE, when the first evidence of settled life appears in the Marmara Region, to 6000 BCE, when Neolithic habitation at the site ceases. Using pottery sherds diagnostic by vessel category and type, this paper aims at identifying which ones may have been primarily used to store, process, or consume dairy products. Organic residue analysis of selected samples helped address the process of adoption and intensification of milk processing in this region over time. The lipid residue data discussed in this paper derive from 143 isotopic results subsampled from 173 organic residues obtained from 805 Neolithic potsherds and suggest that bowls and four-lugged pots may have been preferred containers for processing milk. The discovery of abundant milk residues even among the earliest ceramics indicates that the pioneer farmers arrived in the region already with the knowhow of dairying and milk processing. In fact, these skills and the reliance on secondary products may have given them one of the necessary tools to successfully venture into the unfarmed lands of Northwest Anatolia in the first place.